Deterministic Factor Analysis of Supply Chain Management Characteristic for Oil Companies - Alexey Kirpiko; Amira Gazizova; Regina Khusnutdinova (International Journal of Supply Chain Management, 2020)
Abstract— The subject area of the research work, which determined the key aspects of its meaningful content, was the algorithms for the analytical diagnosis of indicators of Supply Chain Management (SCM) characteristic for the companies operating in the oil sector of the world economy. A generalization of the terms of the methodological tools for conducting a retrospective assessment of the studied indicator formed the basis for the argumentation in favour of the benefits of using the deterministic factor analysis model. They are caused by the possibility of a substantive economic interpretation of the factorial features included in its structure and reflecting changes in the results of operating and financial activities of corporations, as well as the pronounced relationship of the formalized algorithm used in the work with the format for disclosing financial indicators in the public reporting of the economic entities. The composition of factorial features formalized in the content of the mathematical model included the indicator of sales profitability for operating activities, the indicator of total assets turnover, the amount of financial leverage, the effect of financial transactions, and the levels of credit and tax burden of a company. Analytical processing of the results implied the integration of the results obtained for the dynamic assessment of supply chain management in the context of economic diagnostics, as well as the study of the homogeneity of cause-effect relationships for the dynamics of the analysed indicator under the influence of eliminated factors of the model when companies of one type of economic activity belong to different national economic systems.